SIMULASI TRAJECTORY PLANNING DAN PEMBENTUKAN FORMASI PADA ROBOT OBSTACLE AVOIDANCE - Suparno, Aditya Prima; Widyantara, Helmy; Harianto, Harianto (Journal of Control and Network Systems, 2015)
The defense system of the country has developed a technology which has an intelligence and an accuracy level that are high enough to help maintain the stability of the country in a more optimal state. The Cavalry Battalion combat vehicles, as one of the examples, is used to attack and demolish the enemyâs base by constructing a special formation in its movement towards the attack position based on the command of the leader in the front line. Based on the existing development of the technology, in this study, a simulation of the robot colony movement was made before the real implementation stage. In the simulation, the movement of the robot colony was designed like a Cavalry Battalion formation when it determines a track to its attack position. The colony was created by using 3 robotic simulation. The methods used included fuzzy Sugeno, robotic formation, and obstacle avoidance. The formation creation based on the instruction of the robotâs leader before and after passing the obstacle could be done by sending the coordinates of the destination which was done by the robotâs leader, coordinating the speed which was made based on the distance of each robot to another robot, and enabling the robots ability to provide the movements decision itself when it passed through the obstacle. The average errors of follower robot A toward the target goal given by its leader of the X-axis was 4,834%, and 1,905% on the Y axis. The average error of follower robot B the target goal given by its leader of the X-axis was 3,974% and 2,415% on the Y axis.